Modelo de evaluación del desempeño social cooperativo y buen vivir en la Cooperativa de Ahorro y Crédito Calceta LTDA. - Vera Rivas, María Ángeles (2020)
Considering that the savings and credit cooperatives, in addition to carrying out their financial intervention activity, are in the commitment and duty of establishing social actions linked to the community and thus improving the quality of life of their members, an evaluation model of cooperative social performance and good living was carried out in Cooperativa de Ahorro y Crédito Calceta Ltda. For this, surveys and interviews were applied to its governing bodies (Board of Directors, Supervisory Board and Manager), with which showed that the Cooperative has developed various social actions but that they have lacked a follow-up or control to corroborate that these were carried out. After that, the indicators were selected by experts, which were subjected to a weighting process both in the context of partners and cooperatives through the Hierarchical Analytical Process (AHP), in addition, a traffic light matrix was elaborated by indicator in order to determine the level of performance based on scores and colors. Likewise, the information related to the selected indicators was requested from the cooperative with the end of 2019 and a survey was applied to members, information that was tabulated and analyzed; these results were compared with the score raised in the traffic lights and multiplied by the final weighting of the Hierarchical Analytical Process. In which it was identified that from the 22 indicators, 7 reflect an unsatisfactory performance and therefore actions are proposed to counteract the shortcomings.